A contribuição da linguagem da arte nos espaços do terceiro setor da cidade de São Paulo - Santiago, Maria Cecilia do Amaral Campos de Barros (2014)
The survey s purpose is to study the art practices in the Third Sector entities Nova União da Arte and De Olho no Futuro, analyzed with a focus on Triangular Methodology, by Ana Mae Barbosa. The objectives are to identify the practices involving art used in the social projects chosen; verify how art is being addressed by leaders and educators and understand how young people participating in social projects find a place for art in their lives. The research methodology used to achieve these tasks was bibliographic review and documentary survey of quantitative trait to identify the Third Sector entities in São Paulo working with art in the cropping period (2000-2010). The field research was conducted in the selected entities with semi-open interviews with leaders, educators and young people participating in social projects. The result shows the potential of the work involving art as a way to build values and strengthening self-esteem, seeking a new critical eye on the world, once art provides knowledge about themselves and each other.